Economic Studies - A. V. Kholopov (Vestnik MGIMO-Universiteta)
The establishment of the School of Economic Science at MGIMO was due to the necessity of the world economy research, and the need to prepare highly skilled specialists in international economics. The school is developing a number of areas, which reflect the Faculty structure. - Economic theory is one of the most important research areas, a kind of foundation of the School of Economic Science at MGIMO. Economic theory studies are carried out at the chair of Economic theory. "The course of economic theory" textbook was published in 1991, and later it was reprinted seven times. Over the past few years other textbooks and manuals have been published, including "Economics for Managers" by Professor S.N. Ivashkovskaya, which survived through five editions; "International Economics" - four editions and "History of Economic Thought" - three editions. - International Economic Relations are carried out by the Department of International Economic Relations and Foreign Economic Activity. Its establishment is associated with the prominent economist N.N. Lyubimov. In 1957 he with his colleagues published the first textbook on the subject which went through multiple republications. The editorial team of the textbook subsequently formed the pride of Soviet economic science - S.M. Menshikov, E.P. Pletnev, V.D. Schetinin. Since 2007, the chair of Foreign Economic Activities led by Doctor of Economics, Professor I. Platonova has been investigating the problems of improving the architecture of foreign economic network and the international competitiveness of Russia; - The history of the study of problems of the world economy at MGIMO begins in 1958 at the chair baring the same name. Since 1998, the department has been headed by Professor A. Bulatov; - The study of international monetary relations is based on the chair of International Finance, and is focused on addressing the fundamental scientific and practical problems; - The chair "Banks, monetary circulation and credit" was created in February 2012. It is head by Professor G.S. Panova. The members of the chair are experienced bank employees; - The field of practical application of research results in the field of accounting, statistics and auditing has been expanding in recent years. The research in the field is conducted at the synonymous chair; - An important direction of development of economic studies at MGIMO is a risk management and insurance. Established in 1993, the Department of Risk Management and Insurance is headed by Professor R.T. Yuldashev.